Preparation method of nano cerium oxide
Through the new sol-gel precipitation method, the problems of serious agglomeration and insufficient dispersion in the preparation of nano cerium oxide powder were solved, and the uniformity and excellent performance of nano cerium oxide particles were achieved. The process was simple and environmentally friendly, and it was suitable for large-scale production.
Patent Information
- Application Number
- CN202411737381.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nano cerium oxide powder preparation process has problems such as serious agglomeration and insufficient dispersion, resulting in uneven particle sizes of prepared cerium oxide particles, irregular morphology, complex process and unfriendly to the environment.
A new sol-gel precipitation method is adopted. By uniformly mixing the hydrophilic colloid with water, adding soluble cerium salt and regulator, solution A and solution B are formed, and after mixing, the precipitant solution is added dropwise, and after reaction, it is dried and crushed. and calcined at high temperature to prepare nano cerium oxide.
The uniform particle size distribution, good dispersion and excellent performance of nano cerium oxide particles is achieved. The process is simple, low cost, pollution-free, environmentally friendly, and suitable for large-scale preparation.
Smart Images

Figure CN119461456A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing nano cerium oxide, and belongs to the field of nano powder preparation. Background Art
[0002] Chemical mechanical polishing is one of the key technologies for the manufacture of high-precision optical devices and integrated circuits. The core of chemical mechanical polishing is polishing abrasives with controllable physical properties and chemical composition. Rare earth polishing powder has the characteristics of fast polishing speed and high precision. Since its invention and application, the production process has changed with the progress of rare earth separation technology. Cerium dioxide is widely used in various functional materials due to its excellent redox ability. It has been widely used in the fields of catalysis, polishing, energy conversion, etc., especially cerium-based grinding materials are widely developed and applied as grinding materials for glass materials. In recent years, with the rapid development of information industry and industry manufacturing technology, the requirements for polishing and grinding of liquid crystal displays, flat panel displays, optical components and electrical and electronic equipment are getting higher and higher, requiring faster grinding speeds and better surface accuracy, and at the same time, the grinding materials need to have better recycling performance.
[0003] In recent years, researchers have tried to develop a variety of methods to synthesize submicron and nano-scale cerium oxide with multiple scales and large specific surface areas, mainly including: solid phase method, liquid phase method and gas phase method. The solid phase method is to prepare samples through solid-solid reaction under high temperature conditions. The solid phase method is easy to mix with impurities, resulting in insufficient purity and difficult to control the particle size distribution range; the liquid phase method mainly includes precipitation method, sol-gel method and microemulsion method. The liquid phase method is prone to agglomeration and pollution; the gas phase method refers to a method in which two or more elements or compounds react chemically in the gas phase to generate compounds. The reaction conditions of the gas phase method are quite harsh and the reaction is difficult to control.
[0004] The Chinese invention patent application with application number 201210435552.6 proposes a method for preparing a high specific surface area cerium dioxide material, which comprises dissolving cerium salt and citric acid in a solvent to obtain a cerium citric acid precursor; dissolving CTAB in a solvent to prepare a CTAB solution; slowly adding the CTAB solution to the cerium citric acid precursor, stirring at 65-70°C until the mixed solution becomes a gel, then drying, washing with anhydrous ethanol and deionized water, and calcining after drying to obtain a cerium-based catalyst material with a high specific surface area. This method adds acid and a dispersant to generate a gel by hydrothermal reaction, and uses ammonia water to adjust the pH value. The reaction operation is relatively complicated and the irritating odor of ammonia water is relatively large.
[0005] The Chinese invention patent application with application number 201310671603.X proposes a method for preparing mesoporous cerium oxide powder by sol-gel method, using a mixed solution composed of ethanol, acetic acid, butanediol and citric acid as a template; providing a new synthesis route for the synthesis of mesoporous cerium oxide powder, the formation conditions of the gel are that the mixed solution and the cerium nitrate solution are stirred at 60-80℃ for 2-4h, then kept at 60-70℃ for 2.5-5h, and the gel is heated to 400-450℃ and kept for 0.5-1h to obtain the mesoporous cerium oxide powder. This method uses acid and alcohol as a template mixed solution to react with cerium nitrate to prepare gel, uses a large variety of raw materials and involves acid and alcohol, which is easy to cause damage to the human body and the environment.
[0006] The Chinese invention patent application with application number 201810813603.1 proposes a method for preparing CeO2 ceramic microspheres by copolymerization-assisted internal gelation, wherein cerium citrate, hexamethylenetetramine, urea, N,N-methylenebisacrylamide, acrylic acid and ammonium persulfate are mixed to obtain a precursor solution; the precursor solution is dispersed in silicone oil to obtain gel balls, and the gel balls are calcined to obtain cerium dioxide microspheres. The microspheres are porous, with a particle size of 300 to 600 microns, and are used in the field of nuclear energy. This method uses a variety of organic compounds as precursors and silicone oil as a gel medium, which is unfriendly to the human body and the environment, is prone to by-products, and has low purity. It is prepared into microspheres of 300-600 microns, and has limited application areas.
[0007] The Chinese invention patent application with application number 201811587542.8 proposes a method for preparing nano-cerium oxide particles, which includes preparing a cerium nitrate-complexing agent aqueous solution, adjusting the pH, stirring to form a sol, dispersing the sol as the aqueous phase in a mixture of a surfactant, a co-surfactant and cyclohexane to form a stable reverse microemulsion, and obtaining gel particles through reaction. The gel particles are cooled and frozen, filtered, dried and calcined to obtain 30-80 nanometer cerium oxide particles. This patent uses acid and alkali to adjust the pH value, and uses surfactants and organic matter to react with gel, and also needs to be cooled and frozen. The operation is complicated, the equipment requirements are high, and it is not environmentally friendly; the size of the prepared cerium oxide particles is not very uniform, and the morphology is not very regular.
[0008] The Chinese invention patent application with application number 202011564746.7 proposes a method for synthesizing cerium oxide and a method for using the same, wherein a cerium source aqueous solution is added to a soluble alkaline precipitant aqueous solution to generate a raw material solution, the solution is stirred for precipitation reaction, the raw material solution is filtered, and a gel cerium hydroxide is obtained, the gel cerium oxide dispersion is prepared, an oxidant such as hydrogen peroxide is added to the dispersion, and the dispersion is placed in a closed container for heating reaction, and the prepared cerium oxide is used for chemical mechanical polishing. This method requires the use of nitrogen as a protective gas, a strong base such as sodium hydroxide, and a closed environment for a certain period of time to react. It has high requirements on equipment, and the operation is cumbersome, which is not friendly to the human body and the environment.
[0009] The Chinese invention patent application with application number 202210200404.X proposes a method for preparing nano-cerium oxide by sol-gel method, in which an organic precipitant is added to a high-concentration inorganic cerium salt to react to generate a cerium hydroxide precipitate, and the organic precipitant is continued to be added until the cerium hydroxide precipitate is completely dissolved. After the solution is clarified, it is heated to 50-60°C to generate a wet gel; the wet gel is washed and filtered and placed in an oven at 120-200°C, dried for 24-36 hours, and the water is removed to obtain a dry gel; the dry gel is calcined at 650-750°C for 4 hours to obtain 50-150 nanometers of cerium oxide. This method uses an organic precipitant, which is not environmentally friendly, has a long drying time, high energy consumption, and the prepared cerium oxide particles have a large particle size.
[0010] Cerium oxide prepared without high temperature treatment usually has incomplete crystal form, low particle formation, and often has porous or mesoporous grid structures, which makes it impossible to use in the process of chemical mechanical polishing; the cerium oxide powder particles and agglomeration phenomenon obtained by high temperature treatment are very serious, and the depolymerization and dispersion process is complicated during subsequent use. At present, most patented technologies use cerium chloride, cerium nitrate or cerium carbonate dissolved in acid and then used, and need to add dispersants, regulators, and organic reagents to adjust the pH value for precipitation. Most sol-gel methods use organic matter, acid, and dispersant to react to generate sol-gel. The process is complicated and a lot of highly corrosive, toxic, harmful and polluted tail gas or waste liquid will be generated during the preparation process, which is extremely harmful to equipment and the environment, and increases the cost of equipment and environmental protection. Therefore, it is of great significance to develop a simpler, more efficient, low-cost and pollution-free sol-gel precipitation method to synthesize nano-sized, uniformly distributed and excellent nano-cerium oxide. Summary of the invention
[0011] In view of the shortcomings of the prior art, the object of the present invention is to provide a simpler method for preparing nano-cerium oxide.
[0012] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0013] A method for preparing nano cerium oxide comprises the following steps:
[0014] S1, mixing the hydrophilic colloid and water uniformly to obtain solution A;
[0015] Mixing the soluble cerium salt, the regulator and water uniformly to obtain a solution B;
[0016] Wherein, the regulator is a water-soluble chloride salt;
[0017] S2, mixing solution A and solution B uniformly to obtain solution C; preferably, adding solution B dropwise into solution A and mixing uniformly;
[0018] S3, adding a precipitant solution dropwise to the solution C, and after the reaction, performing solid-liquid separation to obtain a precipitate;
[0019] S4. The precipitate is dried, crushed and calcined in sequence to obtain nano cerium oxide.
[0020] Furthermore, solution A is in a sol state.
[0021] Furthermore, in S1, the hydrophilic colloid includes one or more of xanthan gum, guar gum, and carrageenan; the regulator includes one or more of sodium chloride, potassium chloride, and ammonium chloride; and the soluble cerium salt includes one or more of cerium nitrate, cerium chloride, and cerium sulfate.
[0022] Furthermore, in S1, the mass of the hydrophilic colloid in solution A is 0.1-5% of the mass of water, preferably 0.5-4.5%, more preferably 1-4%, and even more preferably 1.5-3.5%; the applicant has found that controlling the proportion of hydrophilic colloid can make the viscosity of solution A moderate, achieve good dispersion of soluble cerium salt, and improve the quality of the final nano-cerium oxide; too low or too high a proportion is not conducive to the dispersion of soluble cerium salt.
[0023] Preferably, the hydrophilic colloid and water are uniformly mixed at 25-70° C., preferably at 40-65° C., more preferably at 45-60° C.; thereby, the dissolution of the hydrophilic colloid can be accelerated and the hydrophilic colloid can be prevented from decomposing and denaturing due to excessive temperature.
[0024] Preferably, the mixing time of the hydrophilic colloid and water is 90-240 min, preferably 110-210 min, more preferably 130-200 min, and even more preferably 150-200 min, to ensure sufficient dissolution of the hydrophilic colloid.
[0025] Furthermore, in S1, the molar ratio of cerium ions in the soluble cerium salt to chloride ions in the regulator is 1:3-6, preferably 1:3.5-5.5, and more preferably 1:4-5; preferably, the total mass ratio of the soluble cerium salt and the regulator to the mass ratio of water is 1:8-40, preferably 1:10-30, and more preferably 1:12-20. Thus, by controlling the molar ratio of cerium ions in the soluble cerium salt to chloride ions in the regulator, the molar number of chloride ions can be matched with the molar number of cerium ions, which has a better anti-precipitation effect; too little will easily lead to partial precipitation of the hydrophilic colloid, affecting the final preparation effect; too much will lead to waste of the regulator and increase the burden of subsequent waste liquid treatment, which is not conducive to cost reduction and efficiency improvement. By controlling the total mass ratio of the soluble cerium salt to the regulator and the mass ratio of water, the regulator and the soluble cerium salt can be fully dissolved, and the concentration of the regulator and the soluble cerium salt can be moderate so as to better disperse and combine with the hydrophilic colloid, while the concentration of the hydrophilic colloid will not be too sparse after mixing solution A and solution B, which will make it difficult to play the role of gel sol.
[0026] Furthermore, solution C is in a transparent sol state.
[0027] Furthermore, in S2, the mass ratio of the soluble cerium salt in solution B to the hydrophilic colloid in solution A is 1:0.05-2.5, preferably 1:0.052-2. The molecular weight of the hydrophilic colloid is relatively large, and only a small amount is needed to achieve the attachment and dispersion of cerium ions. Controlling the appropriate ratio is conducive to the full dispersion of the cerium salt; when the amount of hydrophilic colloid added is too low, it is not conducive to the full action of the chemical bond between the cerium ion and the oxygen atom, which may lead to insufficient dispersion and affect the quality of the final nano cerium oxide.
[0028] Further, in S2, solution B is added dropwise into solution A; preferably, the solution is added dropwise while stirring; preferably, the dropwise acceleration rate is controlled to be 0.2-0.8 ml / s to achieve sufficient dispersion and ensure efficiency.
[0029] Generally, in S3, a white sol-gel is formed during the dropwise addition process. The precipitate is white.
[0030] Furthermore, in S3, the mass ratio of the precipitant to water in the precipitant solution is 1:20-200, preferably 1:25-150, more preferably 1:30-100, and more preferably 1:35-60. Thus, the precipitant can be fully dissolved in water, and the appropriate precipitant concentration can be controlled to make the precipitation process rate moderate, thereby improving the uniformity of the obtained nano-cerium oxide; too little water can easily lead to too high a precipitant concentration, and the precipitation process is too intense, resulting in unevenness; too much water can easily lead to the collapse of the sol-gel system, which cannot play an ideal role and is not conducive to improving efficiency.
[0031] Furthermore, in S3, the precipitant is a soluble oxalate, and more preferably, the soluble oxalate includes one or more of ammonium oxalate, sodium oxalate, and potassium oxalate.
[0032] Furthermore, in S3, the molar ratio of cerium ions in solution C to oxalate ions in the added precipitant solution is 2:3-6, preferably 2:3.5-5.5. Thus, cerium ions in solution C can be fully precipitated; if the amount of oxalate ions is too small, cerium ions cannot be completely precipitated, and after drying, cerium exists in the form of precipitated cerium salt and soluble cerium salt, resulting in two different cerium oxides.
[0033] Further, in S3, the drying temperature is 70-85°C, preferably 75-80°C;
[0034] Preferably, static heating drying is performed using a hot blast box;
[0035] Preferably, the calcination temperature is 600-900°C, preferably 700-850°C, and the calcination time is 60-120min, preferably 70-100min; more preferably, during calcination, the heating time is controlled to be 60-120min, preferably 80-100min.
[0036] The present invention aims at solving the problems of serious agglomeration and insufficient dispersibility in the existing cerium oxide powder preparation process, and proposes a method for preparing nano cerium oxide powder with excellent dispersibility by a novel sol-gel precipitation method. The cerium oxide particles prepared by the preparation method of the present invention are nano-scale, have uniform particle size distribution, and are dispersed. The particle agglomerates can be easily deagglomerated and well dispersed in the solution, and can provide high-quality powder materials for many fields requiring highly dispersible powders, such as the nano cerium oxide polishing field.
[0037] After repeated research, the applicant found that by pre-mixing the regulator into solution B, it is possible to effectively prevent the hydrophilic colloid from precipitating from the solution to form a cotton-like precipitate when solution A and solution B are subsequently mixed, thereby preparing for the subsequent precipitation process. The possible reason is that the addition of the regulator can adjust the charge and pH value of the soluble cerium salt to prevent the hydrophilic colloid from precipitating.
[0038] The present invention utilizes the high molecular solubility characteristics of hydrophilic colloids, first dissolves and disperses the hydrophilic colloids in water to form a high molecular chain structure; by adding a regulator, the dissolved cerium ions and the oxygen atoms in the hydrophilic colloids are dispersed in the high molecular structure through the action of chemical bonds, thereby forming a cerium source uniformly distributed in the system, and by adding a precipitant, a single relatively dispersed precipitated cerium salt molecule is formed at the cerium source with cerium as the core, and then calcined by high temperature heating, the dispersed precipitated cerium salt forms nano cerium oxide. The method proposed by the present invention of directly using hydrophilic colloids to form sol-gels to disperse soluble cerium salts, and then precipitating and calcining to prepare nano cerium oxide is more direct and simple compared to other existing sol-gel methods, and does not use acids, alkalis, organic matter and other substances as reaction raw materials, is simple to operate, low cost, pollution-free, environmentally friendly, easy to prepare in large quantities, and the prepared nano cerium oxide is strong in dispersibility, wide in application field, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a process flow chart for preparing nano cerium oxide.
[0040] Figure 2 This is one of the SEM images of nano-cerium oxide obtained in Example 1.
[0041] Figure 3 This is the second SEM image of the nano-cerium oxide obtained in Example 1.
[0042] Figure 4 This is a SEM image of nano-cerium oxide obtained in Example 2.
[0043] Figure 5 This is a SEM image of nano-cerium oxide obtained in Example 3.
[0044] Figure 6 This is the SEM image of nano-cerium oxide obtained in Comparative Example 1.
[0045] Figure 7 This is the SEM image of nano-cerium oxide obtained in Comparative Example 2.
[0046] Figure 8 This is the SEM image of nano-cerium oxide obtained in Comparative Example 3. DETAILED DESCRIPTION
[0047] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0048] Example 1
[0049] Take 20g of deionized water, heat it at 60℃ on a heating stirrer for 60min, weigh 20mg of xanthan gum, add xanthan gum while stirring, and continue stirring for 180min until the xanthan gum dissolves to form a sol (solution A). Weigh 375mg of cerium nitrate and 10g of deionized water, dissolve the cerium nitrate in deionized water, then weigh 152mg of sodium chloride, add it to the obtained cerium nitrate solution, and stir to dissolve until a colorless and transparent solution B is formed. Add solution B dropwise to the dissolved solution A, stirring and dropping until a transparent solution C is formed. Take 185mg of ammonium oxalate, dissolve it in 10g of water, and obtain a precipitant solution; then add the precipitant solution dropwise to solution C, and the solution forms a white sol, and further until a white precipitate is generated, and solid-liquid separation is obtained to obtain a precipitate. Then, the precipitate is placed in a hot blast box at 85°C for drying. The dried precipitate is taken out, ground, and placed in a corundum crucible, which is then placed in a muffle furnace. The temperature is raised to 800°C (heating time is 120 minutes), kept at this temperature for 60 minutes, and cooled with the furnace to obtain a porous branched chain structure, easily dispersed, with a size of about 30 nanometers, and uniform size distribution of cerium oxide particles. Figure 2 and Figure 3 .
[0050] Example 2
[0051] Example 1 was repeated, except that 375 mg of cerium nitrate and 5 g of deionized water were weighed, the cerium nitrate was dissolved in the deionized water, and then 152 mg of sodium chloride was weighed and added to the obtained cerium nitrate solution, and stirred to dissolve until a colorless and transparent solution B was formed. 185 mg of ammonium oxalate was taken and dissolved in 5 g of water to obtain a precipitant solution.
[0052] See also Figure 4 The final product is a cerium oxide particle powder with a porous branched chain structure, easy to disperse, a size of about 40 nanometers, and a uniform size distribution.
[0053] Example 3
[0054] Example 1 was repeated, except that the amount of sodium chloride added was 304 mg; the amount of ammonium oxalate added was 370 mg.
[0055] See also Figure 5 The final product is a cerium oxide particle powder with loose particles, good dispersion and a size of about 50 nanometers.
[0056] Comparative Example 1
[0057] Weigh 375 mg of cerium nitrate and 10 g of deionized water, dissolve the cerium nitrate in deionized water to obtain solution B. Take 185 mg of ammonium oxalate and dissolve it in 10 g of water to obtain a precipitant solution. Then add the precipitant solution dropwise to solution B, and the solution forms a white sol containing suspended precipitates, and the solid-liquid separation is performed to obtain a precipitate. The precipitate is placed in an 85°C hot blower to dry, the dried precipitate is taken out and ground, and placed in a corundum crucible, placed in a muffle furnace, heated to 800°C from room temperature for 120 min, kept warm for 60 min, and cooled with the furnace to obtain a cerium oxide powder with unformed particles and large-area flakes, see Figure 6 .
[0058] Comparative Example 2
[0059] Take 20g of deionized water, heat it at 60℃ on a heating stirrer for 60min, weigh 20mg of xanthan gum, add xanthan gum while stirring, and continue stirring for 180min until the xanthan gum dissolves to form a sol (solution A). Weigh 375mg of cerium nitrate and 10g of deionized water, dissolve cerium nitrate in deionized water to obtain solution B. Add solution B dropwise to solution A, stirring and adding dropwise, continue stirring and reacting for 3min after the addition is complete, floccules will precipitate, and with the precipitation of floccules, the sol-gel with good fluidity will become a clear solution to obtain a mixed solution system. Take 185mg of ammonium oxalate, dissolve it in 10g of water, and obtain a precipitant solution; then add the precipitant solution dropwise to the aforementioned mixed solution system, the solution forms a white precipitate, and the solid-liquid separation is obtained to obtain a precipitate. The precipitate was placed in a hot blast box at 85°C for drying. The dried precipitate was taken out and ground, then placed in a corundum crucible, and then placed in a muffle furnace. The temperature was raised to 800°C (heating time was 120 min), and the temperature was kept for 60 min. The cerium oxide powder with a few particles and large-area flakes was obtained. Figure 7 .
[0060] Comparative Example 3
[0061] Take 20g of deionized water, heat it at 60℃ on a heating stirrer for 60min, weigh 20mg of xanthan gum, add xanthan gum while stirring, and continue stirring for 180min until the xanthan gum dissolves to form a sol (solution A). Weigh 375mg of cerium nitrate and 10g of deionized water, dissolve the cerium nitrate in deionized water, then weigh 152mg of sodium chloride, add it to the cerium nitrate solution, and stir to dissolve until a colorless and transparent solution B is formed. Add solution B dropwise to solution A, stirring and dropping until a transparent solution C is formed. Take 18.5mg of ammonium oxalate, dissolve it in 10g of water, and obtain a precipitant solution; then add the precipitant solution dropwise to solution C to form a white sol-like substance in the solution, and further until a white precipitate is generated, and separate the solid and liquid to obtain a precipitate. The precipitate was placed in a hot blast oven at 85°C for drying. The dried precipitate was taken out and ground, then placed in a corundum crucible, and then placed in a muffle furnace. The temperature was raised to 800°C (heating time was 120 min), and the temperature was kept for 60 min. The cerium oxide powder with a partially granular structure of 50 nm and a partially flaky structure was obtained. Figure 8 .
[0062] In summary, the preparation method of the present invention can be used to obtain nano cerium oxide with excellent performance in various aspects such as morphology and size. The contents of the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, the modifications of various equivalent forms of the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing nano cerium oxide, characterized in that: The steps include: S1, mixing the hydrophilic colloid and water evenly to obtain solution A; Mix the soluble cerium salt, the regulator and water to obtain solution B; Wherein, the regulator is a water-soluble chloride salt; S2, mixing solution A and solution B evenly to obtain solution C; S3, adding a precipitant solution dropwise to the solution C, and after the reaction, performing solid-liquid separation to obtain a precipitate; S4. The precipitate is dried, crushed and calcined in sequence to obtain nano cerium oxide.
2. The preparation method according to claim 1, characterized in that: In S1, the hydrophilic colloid includes one or more of xanthan gum, guar gum, and carrageenan; the regulator includes one or more of sodium chloride, potassium chloride, and ammonium chloride; and the soluble cerium salt includes one or more of cerium nitrate, cerium chloride, and cerium sulfate.
3. The preparation method according to claim 1, characterized in that: In S1, the mass of the hydrophilic colloid in solution A is 0.1-5% of the mass of water, preferably 0.5-4.5%, more preferably 1-4%, and even more preferably 1.5-3.5%; preferably, the hydrophilic colloid and water are uniformly mixed at 25-70° C., preferably at 40-65° C., and more preferably at 45-60° C.; Preferably, the mixing time of the hydrophilic colloid and water is 90-240 min, preferably 110-210 min, more preferably 130-200 min, and even more preferably 150-200 min.
4. The preparation method according to claim 1, characterized in that: In S1, the molar ratio of cerium ions in the soluble cerium salt to chloride ions in the regulator is 1:3-6, preferably 1:3.5-5.5, and more preferably 1:4-5; preferably, the mass ratio of the total mass of the soluble cerium salt and the regulator to the mass of water is 1:8-40, preferably 1:10-30, and more preferably 1:12-20.
5. The preparation method according to claim 1, characterized in that: In S2, the mass ratio of the soluble cerium salt in solution B to the hydrophilic colloid in solution A is 1:0.05-2.5, preferably 1:0.052-2.
6. The preparation method according to claim 1, characterized in that: In S2, solution B is added dropwise into solution A; preferably, the solution is added dropwise while stirring; preferably, the dropwise acceleration rate is controlled to be 0.2-0.8 ml / s.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In S3, the mass ratio of the precipitant to water in the precipitant solution is 1:20-200, preferably 1:25-150, more preferably 1:30-100, and more preferably 1:35-60.
8. The preparation method according to any one of claims 1 to 6, characterized in that: In S3, the precipitant is a soluble oxalate, and more preferably, the soluble oxalate includes one or more of ammonium oxalate, sodium oxalate, and potassium oxalate.
9. The preparation method according to claim 8, characterized in that: In S3, the molar ratio of cerium ions in solution C to oxalate ions in the added precipitant solution is 2:3-6, preferably 2:3.5-5.
5.
10. The preparation method according to any one of claims 1 to 6, characterized in that: In S3, the drying temperature is 70-85°C, preferably 75-80°C; Preferably, static heating drying is performed using a hot blast box; Preferably, the calcination temperature is 600-900°C, preferably 700-850°C, and the calcination time is 60-120min, preferably 70-100min; more preferably, during calcination, the heating time is controlled to be 60-120min, preferably 80-100min.
Citation Information
Patent Citations
Method for preparing cerium dioxide material with high specific surface area
CN102923753A
Method for preparing mesoporous cerium oxide powder by using sol-gel method
CN103641148A
Method for preparing CeO2 ceramic microspheres by copolymerization-assisted internal gelation
CN109133920B
Preparation method of nano-CeO2 particles
CN109678193A
Method for preparing nano cerium oxide by sol-gel method
CN114477264A
Cited By
Hydrophilic cerium oxide nanosphere as well as preparation method and application thereof
CN120440931A